KERAJAAN ALLAH DALAM INJIL LUKAS: PERUMPAMAAN TENTANG PELITA (LUKAS 8:16-18) - Adi Hardani; Sinta Puji Astuti, Agung Pramana, Sarmauli (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
This study explores the parable of the lamp in the Gospel of Luke as a significant representation of the importance of demonstrating faith and God's blessings to others in embracing the Kingdom of God. Through an in-depth literature review, this research aims to understand the meaning of the lamp parable in the context of the Kingdom of God and identify concrete ways to implement it in everyday life. Using a literature-based approach, various theological perspectives and interpretative methods regarding the lamp parable are examined, along with an analysis of its practical applications in the lives of believers. The findings underscore the importance of being witnesses for Christ by illuminating the world with His truth and love, as well as providing opportunities for others to deepen their knowledge of Him through teaching, Christian example, service, community involvement, and Christian character.